Computer investigation on direct drive shaftless propulsion system for marine application - Ong, Weilun. (2009)
Existing studies on direct shaft propellers have determined its limitations to overcome size and weight issues for marine applications. This work presents the research on direct shaftless propeller to validate its application for marine using computational model. The prototype for direct shaftless propeller and its mechanical calculations are derived using Pro/Engineer. Gambit is used to perform meshing on the prototype, after which, is being exported to Fluent. A simulation is run using defined boundary conditions to determine the location of its highest velocity magnitude and maximum static pressure. It has been observed that the highest velocity magnitude falls on the tip of the blades and the maximum static pressure is located at the origin. The results show negative high pressure at the center of the blade on the face side. This is valid with reference to other studies.